Impact of changes in primary care attachment: a scoping review - Kamila Premji; Leanda Godfrey; Antoine St-Amant; Jonathan Fitzsimon (Family Medicine and Community Health)
Objectives Primary care attachment represents an inclusive, equitable and cost-effective way of enhancing health outcomes globally. However, the growing shortage of family physicians threatens to disrupt patient–provider relationships. Understanding the consequences of these disruptions is essential for guiding future research and policy. The objectives of this study were to map the existing evidence on the impacts of changes in primary care attachment, identify research gaps and recommend areas for further investigation.Design Scoping review following Joanna Briggs Institute (JBI) guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews checklist. Two researchers conducted all stages of screening, and study quality was assessed using JBI critical appraisal tools. Key themes included causes of attachment change, direction of change and outcomes aligned with the quintuple aim framework. Both qualitative and quantitative findings were synthesised narratively.Eligibility criteria Peer-reviewed, English-language articles published between 1999 and 2024 on primary care attachment changes.Information sources PubMed, Scopus and Web of Science.Results Of 2045 studies screened, 31 met inclusion criteria, with 60% published after 2020. Most studies originated from high-income countries, particularly the USA (35%) and Canada (29%). Attachment losses and transfers were the most frequently studied, while attachment and unattachment durations were less explored. These changes in attachment were consistently shown to impact patients, providers, clinics and the healthcare system, influencing all aims of the quintuple aim framework, including clinical outcomes, healthcare utilisation, costs, equity and patient experience. Commonly assessed outcomes included clinical impact (68%), health equity (48%), patient experience (32%) and costs (23%), with no study assessing provider experience.Conclusions This scoping review maps the published literature on changes in primary care attachment and introduces clarifying terminology. Key research gaps include geographical diversity (lack of studies from low- and middle-income countries), attachment gain (limited research on strategies to reconnect unattached patients), attachment duration (insufficient evidence on long-term health outcomes), economic implications (underexplored costs of physician turnover and disruption), provider experiences (lack of studies on how changes in primary care attachment impact provider burnout, job satisfaction and workload) and patient health outcomes (focus on healthcare utilisation rather than direct health outcomes). These findings underscore the need for further research and offer valuable insights for future studies and policy development.